Utopia and Dystopia in German Literature and Film (Istanbul University Press, 2025)
We are very pleased to introduce our new series, Interdisciplinary Studies on German Philology. Founded in 2024, this series is the result of our shared vision and commitment to deepening and expanding knowledge in the field of German Studies. With this publication series, we aim to make a contribution to the scholarly examination of German Philology while also creating a space for interdisciplinary exchange. Our vision for Interdisciplinary Studies on German Philology is based on the conviction that German Studies, as one of the central humanities disciplines, can benefit from dialogue with other disciplines. Linguistics, semiotics, literary studies, cultural studies, film and media studies, history, philosophy, and many other fields offer diverse perspectives that can enrich and deepen research in German Philology. By bringing together these various approaches, we aim to open new paths of understanding and promote innovative research. The goals of our series are clearly defined. First, we want to provide a platform where outstanding scholarly works can be published, distinguished by high quality and originality. We believe it is crucial to make new and relevant research accessible, thus enriching academic discourse. Second, we strive to promote interdisciplinary exchange. By publishing works that integrate different scholarly approaches and methods, we aim to strengthen collaboration between various fields and create new synergies. Another goal of our series is to support the transfer of knowledge between academia and society. We are convinced that scholarly insights are not only significant within the academic community but also in the broader public sphere. By publishing works that address current social issues and challenges, we aim to contribute to public debate and help solve pressing problems. Interdisciplinary Studies on German Philology is aimed at a wide audience. Scholars, early career researchers, graduate students, and anyone interested in German Studies and related disciplines will find valuable insights and ideas here. We want to facilitate access to the latest research findings and thereby promote exchange and collaboration. In selecting contributions, we place great importance on academic excellence. All submitted works undergo a rigorous double-blind review process in which independent experts assess the quality and relevance of the contributions. Through this blind peer-review process, we ensure that only the best works are published in our series. Therefore, we place great emphasis on transparency and integrity in all aspects of our work. Adhering to academic standards and ethical principles is of utmost importance to us. A special concern for us is the promotion of young scholars. Early-career researchers should have the opportunity to publish their work in our series, thereby advancing their academic careers. In this way, we aim to contribute to the development of German Studies and support the next generation of scholars. Interdisciplinary Studies on German Philology has an international focus. We welcome contributions from around the world and aim to foster a global dialogue on topics in German Studies. Through the international orientation of our series, we want to strengthen the exchange between different academic cultures and traditions, thereby enriching German Philology. Another focal point of our work is digitization and the use of new media. We want to harness the possibilities of the digital world to facilitate access to scholarly knowledge and promote the dissemination of our series. In doing so, we rely on innovative publication formats and technologies to meet the needs of our readers. In pursuit of these objectives, we have decided to dedicate our first volume to German visions of utopia and dystopia.